BRCA Mutation Status Is Not Associated With Increased Hematologic Toxicity Among Patients Undergoing Platinum-Based Chemotherapy for Ovarian Cancer. Issue 1 (1st January 2018) - Kotsopoulos, Joanne; Willows, Karla; Trat, Sandra; Kim, Raymond H.; Volenik, Alexandra; Sun, Ping; Narod, Steven A.; Boyd, Jeffrey; May, Taymaa
Abstract : Objective: Women with an inherited BRCA1 or BRCA2 mutation may have an impaired ability to repair chemotherapy-induced damage as a result of a state of haploinsufficiency and may experience greater treatment-related toxicity. The objective of this study was to compare the hematologic adverse effect profiles associated with platinum-based chemotherapy in ovarian cancer patients with and without germline BRCA mutations. Methods: We conducted a retrospective analysis of patients treated for high-grade serous ovarian cancer at Princess Margaret Cancer Center, Toronto, Ontario between January 2000 and December 2015. We included only women with known BRCA mutation status and who received first-line platinum-based chemotherapy. We compared 3 primary measures of myelosuppression (ie, hemoglobin levels, platelet counts, and neutrophil counts) before each cycle of chemotherapy in patients with and without a BRCA mutation. Results: We included 130 BRCA mutation carriers and 302 noncarriers who met the eligibility criteria. There were no significant differences in baseline hemoglobin levels, neutrophil counts, or platelet counts between the groups ( P ≥ 0.31). We found no significant difference in 3 measures of hematologic toxicity (ie, neutropenia, anemia, or thrombocytopenia) based on BRCA mutation status across all chemotherapy cycles ( P ≥ 0.06). Although BRCA mutation carriers were more likely to experience an absolute neutrophil count below 1.0 × 10 9 /L than noncarriers ( P = 0.02), this did not translate to an increased frequency of dose reduction or dose delay. Discussion: Among women with ovarian cancer, hematologic toxicity does not appear to be more frequent in BRCA mutation carriers than in noncarriers. This is reassuring for clinicians treating ovarian cancer patients with respect to dosing regimens. These findings do not support the hypothesis that a haploinsufficiency phenotype exists with respect to the repair of chemotherapy-induced double-strand DNA breaks in this high-risk population.